A Strategy for Detecting Absorbed Bioactive Compounds for Quality Control in the Water Extract of Rhubarb by Ultra Performance Liquid Chromatography with Photodiode Array Detector - 王杨 黄熙 梁清华 范荣 秦锋 呙勇 闫奎坡 刘维 罗杰坤 李云辉 毛喜莲 刘昭前 周宏灏 (Chinese journal of integrative medicine, 2012)
Objective： To detect absorbed bioactive compounds of the water extract whose pharmacodynamic effect was craniocerebral protection for quality control assessment. Methods： Anthraquinones in water extract of rhubarb （WER）, in cerebrospinal fluid （CSF） of patients with traumatic brain injury （TBI） and in ipsilateral cortex of TBI rats following oral WER were respectively explored by ultra performance liquid chromatography with photodiode array detector （UPLC-PDA） method developed in the present study. The effects of anthraquinones absorbed into injured cortex on superoxidase dismutase （SOD） activity in TBI rats were detected. The antioxidative anthraquinones absorbed into target organ were evaluated for quality control of WER. Results： Anthraquinones in WER were aloe-emodin, rhein, emodin, chrysophanol, and physcion. Only the last anthraquinone was found in CSF and in ipsilateral cortex under this chromatographic condition. Physcion increased SOD activity in TBI rats significantly. Conclusions： Physcion was the main active compound of rhubarb against craniocerebral injury via antioxidant pathway. According to our strategy, the exploration of physcion suggested the possibility of a novel quality control of WER in treating TBI injury.